Tele–Neuro-Ophthalmology: Vision for 20/20 and Beyond. Issue 3 (September 2020) - Ko, Melissa W.; Busis, Neil A.
Abstract : Background: Telehealth provides health care to a patient from a provider at a distant location. Before the COVID-19 pandemic, adoption of telehealth modalities was increasing slowly but steadily. During the public health emergency, rapid widespread telehealth implementation has been encouraged to promote patient and provider safety and preserve access to health care. Evidence Acquisition: Evidence was acquired from English language Internet searches of the medical and business literature and following breaking news on the COVID-19 pandemic and responses from health care stakeholders, including policymakers, payers, physicians, health care organizations, and patients. We also had extensive discussions with colleagues who are developing telehealth techniques relevant to neuro-ophthalmology. Results: Regulatory, legal, reimbursement, and cultural barriers impeded the widespread adoption of telehealth before the COVID-19 pandemic. With the increased use of telehealth in response to the public health emergency, we are rapidly accumulating experience and an evidence base identifying opportunities and challenges related to the widespread adoption of tele–neuro-ophthalmology. One of the major challenges is the current inability to adequately perform funduscopy remotely. Conclusions: Telehealth is an increasingly recognized means of health care delivery. Tele–Neuro-Ophthalmology adoption is necessary for the sake of our patients, the survival of our subspecialty, and the education of our trainees and students. Telehealth does not supplant but supplements and complements in-person neuro-ophthalmologic care. Innovations in digital optical fundus photography, mobile vision testing applications, artificial intelligence, and principles of channel management will facilitate further adoption of tele–neuro-ophthalmology and bring the specialty to the leading edge of health care delivery.